Plasma Phospholipid Polyunsaturated Fatty Acids Across Pregnancy in Relation to Neonatal Size and Adiposity: A Longitudinal Study Within the NICHD Fetal Growth Studies (P11-038-19). (13th June 2019) - Zhu, Yeyi; Li, Mengying; Hinkle, Stefanie; Sun, Qi; Wu, Jing; Rahman, Mohammad; Tsai, Michael; Zhang, Cuilin
Abstract: Objectives: Polyunsaturated fatty acids (PUFAs) are essential for fetal growth and development, yet longitudinal data on objectively measured maternal PUFAs across pregnancy in relation to fetal growth remain elusive. We prospectively and longitudinally investigated plasma phospholipid PUFAs in pregnancy in relation to neonatal size and body composition. Methods: Within the NICHD Fetal Growth Studies-Singleton Cohort (n = 2, 802), individual plasma phospholipid PUFAs were measured in blood samples collected at gestational weeks (GW) 10–14, 15–26, 23–31, and 33–39 in a subset of 321 women. Birthweight (BW) was abstracted from medical records. Neonatal length and skinfolds were measured and fat mass (FM) and % body fat (BF) were estimated by Catalano's formula. We used linear regression models with robust variance and inverse probability weighting to standardize the sample. Results: In late pregnancy at GW 33–39, after adjusting for covariates including prepregnancy body mass index, per unit increase in docosahexaenoic acid (DHA) was related to a 95.3 g (95% CI 33.6, 157.0) greater BW, 0.49 cm (0.09, 0.90) longer neonatal length, 41.2 g (13.6, 68.9) greater FM, and 0.79% (0.21, 1.37) higher BF. As for n-6 PUFAs, at GW 33–39, arachidonic acid per unit increase was associated with a 41.7 g (5.22, 78.3) greater BW and docosatetraenoic acid (DTA) per unit increase was related to a 462.3g (98.0, 826.6) and 145.5 g (12.1, 278.9) greater BW and FM, respectively. The PUFA n-6/n-3 ratio per unit increase at GW 33–39 was significantly related to a 14.6g (–29.2, –0.04) lower FM. Further, associations of n-3 PUFA with neonatal adiposity varied by prepregnancy obesity and exposure window. Total n-3 PUFA per unit increase at GW 23–31 and 33–39 was associated with 0.68-0.78% greater neonatal BF among women without obesity, whereas at GW 10–14 and 15–26 it was associated with 1.07–1.36% lower BF among women with obesity (P-interaction < 0.001). No significant associations were observed for individual PUFAs in early to mid-pregnancy with neonatal body composition, except for positive associations of DHA and DTA at GW 10–14 with BW. Conclusions: Our data suggest that maternal plasma phospholipid PUFAs are implicated in fetal growth and their roles may vary by prepregnancy obesity and timing in pregnancy. Funding Sources: NICHD/NIH.